Assessing Sustainability of Paddy Farmers in Peri-Urban Khulna: An Application of Farmer Sustainability Index - Sultana, Rashmia; Kabir, Kazi Humayun; Hasan, Kamrul; Imran, Sardar Al; Khan, Md. Ayatullah (International Journal of Sustainable Agricultural Research, 2021)
Association of sustainability agriculture and farming practices is somehow closely connected. There are necessary different farming practices for both adjusted and unadjusted PFSI measurement. The study observes practices of paddy farming and if farmers are practicing agriculture sustainably by estimating PFSI in three villages of Gutudia union. The objective is to spot the present agricultural practices and accessible sustainable practices, to examine the sustainability degree at field beneath the present paddy farming systems using PFSI and additionally to identify recommendations. The unit of analysis is 50 farmers and measured on a scale of 0 to 100 and also through Saltiel, Bauder, and Palakovich (1994) index. The results discovers that the average sustainability level which is presumably quite unsustainable this shows the necessity for more extension of correct practices. Chi-square analysis shows that the level of farmers’ awareness toward sustainable agriculture and positive attitude are considerably different with the level of PFSI.